Pemberdayaan Masyarakat Dalam Pemenuhan Gizi Keluarga Melalui Inovasi "NaNgKap (Nugget Kangkung Ikan Kakap)" - TRIWIJAYANTI, RENNY (Khidmah, 2024)
Community Empowerment in Fulfilling Family Nutrition Through the Innovation "NaNgKap (Snapper Water Spinach Nuggets)" Abstract Background: Providing Supplementary Food (PMT) is a program implemented by the government for the toddler age group which is intended as an addition to the main daily food to overcome nutritional problems with a length of time of 90 days. Consuming snapper fish can increase growth in children because it contains omega-3 which plays an important role in growth, especially children's brain intelligence. Snapper fish can be developed to make nuggets which will encourage efforts to prevent stunting, where 100 grams of snapper fish contains 92 kcal of energy, 20 grams of protein, 20 mg of calcium. And the combination with eggs in the ingredients for making nuggets which are high in protein and calcium can help a person's growth. Objective: to provide knowledge about the benefits of balanced nutritional food that is good for consumption by children. Research Method: This community service was carried out at 13 Ulu on January 22 – February 9 2024. There were 15 participants in this community service activity. This activity stage is the implementation stage which is carried out in 3 (three) stages, namely meeting for the implementation and dividing the participants who will take part, preparing the materials needed for the implementation and finally carrying out a demonstration. Research Results: The results found an increase in public knowledge about the benefits of balanced nutritional food that is good for consumption by children. Conclusion: as an illustration, processed NaNgKap (Snapper Water Spinach Nuggets) for the community can have a positive influence, especially in increasing knowledge about fulfilling balanced nutrition for families and communities. Keywords: Nugget, Snapper, Balanced Nutrition